2017
DOI: 10.3390/md15040096
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Applications of Chitosan in Cancer Drug Delivery and Therapy

Abstract: Chitosan is a versatile polysaccharide of biological origin. Due to the biocompatible and biodegradable nature of chitosan, it is intensively utilized in biomedical applications in scaffold engineering as an absorption enhancer, and for bioactive and controlled drug release. In cancer therapy, chitosan has multifaceted applications, such as assisting in gene delivery and chemotherapeutic delivery, and as an immunoadjuvant for vaccines. The present review highlights the recent applications of chitosan and chito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 93 publications
1
33
0
3
Order By: Relevance
“…The results showed that Cs NPs have no effect on the DNA of BT breast cancer cell lines; with % DFI reach to 6.77%, which appear less than negative control 13.6% and in comparison with (++) positive control 36.0% and (++++) control 64.2%. This data suggests that chitosan NPs have no negative effect on the nucleic material of the BT breast cancer cell lines and can be used as gene delivery uptake and that approved with several other recent reported results that have been intensively studied for use of Cs NPs as carriers to deliver various drugs and genes in cancer treatment [31][32][33], and that will be focused on the therapeutic potential of chitosanbased nanoparticles for cancer treatment.…”
Section: Genotoxicity Assay (Dna Fragmentation)supporting
confidence: 68%
“…The results showed that Cs NPs have no effect on the DNA of BT breast cancer cell lines; with % DFI reach to 6.77%, which appear less than negative control 13.6% and in comparison with (++) positive control 36.0% and (++++) control 64.2%. This data suggests that chitosan NPs have no negative effect on the nucleic material of the BT breast cancer cell lines and can be used as gene delivery uptake and that approved with several other recent reported results that have been intensively studied for use of Cs NPs as carriers to deliver various drugs and genes in cancer treatment [31][32][33], and that will be focused on the therapeutic potential of chitosanbased nanoparticles for cancer treatment.…”
Section: Genotoxicity Assay (Dna Fragmentation)supporting
confidence: 68%
“…CGRP is released from the pores in the solution with simple physical adsorption. Chitosan is widely used in medicine, food, and many other areas because of its characteristics as a drug carrier or accessory . Many studies on Chitosan and CPC composites show that Chitosan combined with CPC can improve the CPC surface brittleness .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of numerous functional groups allows for easy modification for use in drug delivery applications. Chitosan nanoparticles can encapsulate chemotherapeutics, genes, peptides, or small molecules, and efficiently deliver the cargo for tumor therapy (Babu & Ramesh, 2017; Layek, Lipp, & Singh, 2015; Patel, Patel, & Patel, 2010). The cationic nature of chitosan is harnessed for gene delivery, as negatively charged nucleic acids readily form complexes with chitosan to form nanoparticles.…”
Section: Types Of Nanoparticles For Therapeutic Deliverymentioning
confidence: 99%